Assessing the Mandarin Language Lecturers’ TPACK in Malang City - Tanisiwa, Jesica Stiphanie; Ginting, Daniel (Jurnal Pendidikan Agama Kristen (JUPAK), 2023)
As a teacher in the 21st century, it is important to have knowledge and skills in utilizing technology in the learning process, according to the curriculum, and to be able to use appropriate teaching strategies that match the characteristics of each student. This article aims to measure the Mandarin language lecturers' proficiency in the city of Malang in mastering the TPACK concept in the learning process. This research is a quantitative study that uses survey methods, with questionnaire and interview instruments. The respondents are Mandarin language lecturers in Malang. Based on the results of this study, the majority of Mandarin language lecturers have moderate TPACK knowledge (78%), with 14% in the high group and 7% in the low group. The implication of this research is the need to enhance the TPACK skills of Mandarin language instructors in Malang's higher education institutions to improve their professional development in integrating technology with effective Mandarin language learning materials and strategies.